2022
DOI: 10.1155/2022/1330928
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Mechanism of Icariin on Hypoxic Ischemic Brain Damage in Neonatal Mice

Abstract: Objective. Our previous results showed that icariin (ICA) could inhibit apoptosis and provide neuroprotection against hypoxic-ischemic brain damage (HIBD) in neonatal mice, but the specific mechanism of its neuroprotective effect remains unknown. This study aims at exploring whether ICA plays a neuroprotective role in apoptosis inhibition by regulating autophagy through the estrogen receptor α (ERα)/estrogen receptor β (ERβ) pathway in neonatal mice with HIBD. Methods. A neonatal mouse model of HIBD was constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Icariin is a flavonoid glycoside extracted from the medicinal plant Epimedium (184). Icariin exerts renal protection through multiple bioactivities such as anti-fibrosis (50, 185), anti-inflammatory (186,187), and anti-oxidative stress (186).…”
Section: The Active Compounds In Attenuating Renal Injury Via Regulat...mentioning
confidence: 99%
“…Icariin is a flavonoid glycoside extracted from the medicinal plant Epimedium (184). Icariin exerts renal protection through multiple bioactivities such as anti-fibrosis (50, 185), anti-inflammatory (186,187), and anti-oxidative stress (186).…”
Section: The Active Compounds In Attenuating Renal Injury Via Regulat...mentioning
confidence: 99%
“…In addition to adult models of ischemia, other investigators have shown that ERα plays a role in neuroprotection during the neonatal period. Ircariin, which is a flavonoid glycoside, exerts a neuroprotective effect both in P7 mice following the Vannucci’s model of HI and in a mouse hippocampal neuronal cell line (HT22) during OGD by activating ERα and reducing apoptosis [ 25 ]. When P6 rat pups or the immature oligodendroglia cell line (OLN-93) is exposed to hypoxia estradiol prevents neonatal oxygen-induced white matter injury [ 26 ].…”
Section: Introductionmentioning
confidence: 99%